Cake & Bakery Business Management Of Besito Village, Gebog District, Kudus Regency - Zahro, Nafi Inayati (Universitas Semarang, 2017)
The most-common real problems encountered by most MSMEs in Indonesia are the low level of productivity, low added value, and low product quality. In order to improve MSME s competitiveness, there is a need to take common steps to lift its technology capability and innovativeness. The goal of IPTEK Bagi Masyarakat program is to realize an economically independent cake and bakery business group through partner assistance in Besito Village to allow them to manage their finance well, maintain their bookkeeping correctly according to standard, perform various innovation utilizing technology, improve their knowledge of the proper business management so that they would be able to improve productivity, efficiency, and prevent themselves from wasting resources. The activity is performed through some assistance, technical meeting, and training on such topics as bookkeeping, proper business management, dissemination of the benefits of IP, trademark, halal labelling, packaging, and cataloging. The dissemination on the importance of business permit from Health Office is also done for it is related to their business line, i.e. food industry. Also included in the topics are marketing from conventional one to the utilization of information technology and also the implementation of Accounting bookkeeping management using MYOB Accounting software.